Factors influencing role preferences in decision-making of healthy women with BRCA1/2 pathogenic variants: subanalysis from a randomised controlled decision coaching trial - Kautz-Freimuth, Sibylle; Shukri, Arim; Stracke, Claudia; Isselhard, Anna; Berger-Höger, Birte; Steckelberg, Anke; Vitinius, Frank; Dikow, Nicola; Kiechle, Marion; Meisel, Cornelia; Wöckel, Achim; Mackelenbergh, Marion Tina von; et al. (BMC cancer, 2025)
Patients who actively engage in their medical decision-making processes can experience better health outcomes. This exploratory study aimed to identify predictors of preferred and actual roles in decision-making in healthy women with BRCA1/2 pathogenic variants (PVs).
Gesehen am 22.10.2025